The Socio-Cultural Significance of Selected Indigenous Visual Artefacts in the Lambussie Traditional Area, Ghana - Kombui Babaaradio; Kquofi Steve; Asante Eric Appau; Adom Dickson (ASEAN Multidisciplinary Research Journal, 2022)
The indigenous arts and the Ghanaian culture are extremely interwoven, inseparable and culture-specific. The study investigated the Socio-cultural significance of selected indigenous visual artefacts of Lambussie Traditional Area with specific focus on woodcarving, blacksmithing, and pottery. The exploratory research method under the qualitative research approach was employed by the researchers. Data were gathered from November, 2021 to May, 2022 from 57 participants consisting of 18 craft professionals and 39 non-professionals. Purposive and Snowball sampling techniques were used and Data collection instruments adapted were interviews, focus group sessions and observation. Findings revealed that the indigenous artefacts are an integral part of the people’s lives, used in ways unique to them. The study further revealed that there is a gradual extinction of some of the artefacts due to western education, religion, and technology which is in turn a major setback to the cultural perpetuation of the people.